Spectroscopic and quantum chemical elucidation of newly synthesized 1-aryl-3-methyl-3-phenylpyrrolidine-2,5-diones as potentional anticonvulsant agents - Petković Cvetković, Jelena; Božić, Bojan; Banjac, Nebojša; Lađarević, Jelena; Vitnik, Vesna; Vitnik, Željko; Valentić, Nataša; Ušćumlić, Gordana (HEMIJSKA INDUSTRIJA (Chemical Industry), 2019)
Novel succinimide derivatives were synthesized from 3-methyl-3-phenylsuccinic acid and substituted anilines under solvent-free conditions using the microwave irradiation. All obtained compounds were characterized by the UV, FT-IR, 1H and 13С NMR spectroscopy as well as by elemental analysis. The influence of the substituent electronic effects on the spectroscopic data has been analyzed applying the Hammett equation. Moreover, a detailed interpretation and comparison of experimentally obtained and theoretically calculated FT-IR, UV and NMR spectra have been performed. DFT calculated data of the investigated succinimides are obtained and analyzed in order to determine their structural, spectroscopic and electronic properties. Furthermore, ADMET factor profiling and in-silico prediction of potential biological activities of novel succinimide derivatives have been performed.